Using Three-Tier Test to Identify the Quantity of Student that Having Misconception on Newton's Laws of Motion Concept - Emi Sulistri; Lisdawati Lisdawati (STKIP Singkawang, 2017)
This study aims to identify students quantity who are having the misconception on Newton's laws of motion concept using a Three-tiered Test. The sampling technique used in this study is purposive sampling technique and has been conducted on 56 students at Senior High School. A three-tier